2010
DOI: 10.1126/science.1179850
|View full text |Cite
|
Sign up to set email alerts
|

The Asynchronous State in Cortical Circuits

Abstract: Correlated spiking is often observed in cortical circuits, but its functional role is controversial. It is believed that correlations are a consequence of shared inputs between nearby neurons and could severely constrain information decoding. Here we show theoretically that recurrent neural networks can generate an asynchronous state characterized by arbitrarily low mean spiking correlations despite substantial amounts of shared input. In this state, spontaneous fluctuations in the activity of excitatory and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

137
1,737
11
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,059 publications
(1,890 citation statements)
references
References 28 publications
137
1,737
11
5
Order By: Relevance
“…This protocol produced exquisite data allowing to show that even nearby neurons, generally thought to be strongly connected and to receive a substantial part of common input showed a very low level of correlation. Similar decorrelation results were reported in the rodent neocortex [55] with the same level of accuracy.…”
Section: Iii2 Decorrelation In Experimental Data and Modelssupporting
confidence: 88%
“…This protocol produced exquisite data allowing to show that even nearby neurons, generally thought to be strongly connected and to receive a substantial part of common input showed a very low level of correlation. Similar decorrelation results were reported in the rodent neocortex [55] with the same level of accuracy.…”
Section: Iii2 Decorrelation In Experimental Data and Modelssupporting
confidence: 88%
“…We apply this strategy separately to brain states of wakefulness (Awake) and Slow-Wave Sleep (SWS). In contrast to the former, the latter is known to be characterized by transients of high activity that modulate the whole population behavior [16]. Consistently, we found that the Ising model does not account for such global oscillations of the network dynamics.…”
supporting
confidence: 74%
“…Conclusions: (i) The pairwise Ising model offers a good description of the neural network activity observed during wakefulness. (ii) By contrast, taking into account pairwise correlations is not sufficient to describe the statistics of the ensemble activity during SWS, where (iii) alternating periods of high and low network activity introduce high order correlations among neurons, especially for inhibitory cells [16]. (iv) This suggests that neural interactions during wakefulness are more local and short-range, whereas (v) these in SWS are partially modulated by internally-generated activity, synchronizing neural activity across long distances [4,16,19].…”
Section: Inference Algorithmmentioning
confidence: 99%
“…Theoretical studies have emphasized that, in a sparsely connected network, the seemingly irregular firing of cells could be the consequence of the balance between excitation and inhibition (27)(28)(29). Similarly, intracellular recordings have revealed a balance between excitatory and inhibitory conductance both in vitro (30) and in vivo (31), they and even shown a possible excess of inhibition in vivo (32).…”
Section: Discussionmentioning
confidence: 99%